Studi Dampak Pengelolaan Kelas Dengan Pendekatan Student Center Learning di SMA Islam Raudlatul Falah - Kusmawati, Heny; Asshofa, Fahmi; Mujtaba, Habib El (AL-BURHAN, 2023)
Teachers must carry out classroom processing to make the class more organized, apart from that, classroom processing can make the learning process more effective and efficient. One way to process classes is to use the Student Center Learning approach. The Student Center Learning approach is an approach that focuses the learning process on students. The aim of this research is to determine the impact of classroom management using the Student Center Learning approach at Raudlatul Falah High School. The data collection methods used were interviews and observation. The research results show that (1) The steps taken in implementing the SCL (Student Centered Learning) approach are selecting problems, making plans, implementing, analyzing, evaluating. (2) The impact of processing classes using the Student Canter Learning approach is that students are more involved, students are more critical in their learning abilities, students are more independent and learning becomes more personalized.Keywords: Impact of Class Management, Student Center Learning Approach